Decreased expression of GRAF1/OPHN-1-L in the X-linked alpha thalassemia mental retardation syndrome - Travali Salvatore; Rappazzo Giancarlo; Castiglia Lucia; Musso Nicolò; Fichera Marco; Ragusa Angela; Barresi Vincenza; Mattina Teresa; Romano Corrado; Cocchi Guido; Condorelli Daniele F (BMC, 2010)
Abstract Background ATRX is a severe X-linked disorder characterized by mental retardation, facial dysmorphism, urogenital abnormalities and alpha-thalassemia. The disease is caused by mutations in ATRX gene, which encodes a protein belonging to the SWI/SNF DNA helicase family, a group of proteins involved in the regulation of gene transcription at the chromatin level. In order to identify specific genes involved in the pathogenesis of the disease, we compared, by cDNA microarray, the expression levels of approximately 8500 transcripts between ATRX and normal males of comparable age. Methods cDNA microarray was performed using total RNA from peripheral blood mononuclear cells of ATRX and normal males. Microarray results were validated by quantitative real-time polymerase chain reaction. Results cDNA microarray analysis showed that 35 genes had a lower expression (30-35% of controls) while 25 transcripts had a two-fold higher expression in comparison to controls. In the microarray results the probe for oligophrenin-1, a gene known for its involvement in mental retardation, showed a decreased hybridization signal. However, such gene was poorly expressed in blood mononuclear cells and its decrease was not confirmed in the quantitative real-time RT-PCR assay. On the other hand, the expression of an homologous gene, the GTPase regulator associated with the focal adhesion kinase 1/Oligophrenin-1-like (GRAF1/OPHN-1-L), was relatively high in blood mononuclear cells and significantly decreased in ATRX patients. The analysis of the expression pattern of the GRAF1/OPHN-1-L gene in human tissues and organs revealed the predominant brain expression of a novel splicing isoform, called variant-3. Conclusions Our data support the hypothesis of a primary role for altered gene expression in ATRX syndrome and suggest that the GRAF1/OPHN-1-L gene might be involved in the pathogenesis of the mental retardation. Moreover a novel alternative splicing transcript of such gene, predominantly expressed in brain tissues, was identified.